ISOLATION AND PARTIAL CHARACTERIZATION OF TWO PROTEASES FROM THE VENOM OF PERUVIAN Loxosceles laeta SPIDER - Huari, Frank (2016)
Two proteases from the glandular venom of Loxosceles laeta spider were isolated using a column of Sephadex G-100 gel molecular filtration equilibrated with 0,05M ammonium acetate buffer pH 5,0. One of them is a metalloprotease inhibited by 5 mM EDTA (60,5%) and the other is a serinoprotease inhibited by 5 mM PMSF (93,3%). The metalloproteinase had activity on casein and dimethylcasein while the serinoprotease had activity on citrated human plasma. They showed different molecular weights by PAGE-SDS: 35 kDa and 15,9 kDa. In addition both were antigenic against commercial loxoscelic antivenom by immunodifusion assays.